Effectiveness of Multilingual Broadcasting: A Case Study of Radio Nepal - Bista, Janardan (Historical Journal, 2023)
Radio Nepal, as the pioneering radio broadcaster of the country, has played a crucial role in serving its listeners for over seven decades. In the earlier years, it was the sole medium of information, education, and entertainment, particularly for rural communities, before the advent of television and FM radios. As a national broadcaster, Radio Nepal has assumed significant national duties and responsibilities that set it apart from other media outlets. In response to the evolving socio-political landscape, Radio Nepal has bolstered its multilingual or inclusive broadcasting by incorporating more native languages into its programming. Currently, it broadcasts news and programs in 21 different languages, in addition to Nepali, aiming to address the linguistic diversity of the nation. This research aims to fill this knowledge gap and assess the impact of Radio Nepal’s inclusive broadcasting from the listener’s perspective. To measure the effectiveness, the research conducted a survey based on Radio Nepal’s initiative to evaluate its inclusive broadcasting. The findings reveal that Radio Nepal’s inclusive broadcasting has been highly effective. Listeners from diverse linguistic communities have shown a growing interest in news and programs broadcast in their native languages. Moreover, broadcasting has successfully transcended linguistic boundaries, reaching beyond specific communities, thereby contributing to the conservation and respect of different languages by the state and society.